A influência das notícias de corrupção no comportamento antiético dos consumidores - Pereira, Natalia Peixoto (2019)
Exposure to corruption cases through medias has been recurrent in the last few years, but little has been investigated as this increasing exposure affects consumer relations. In this study, we sought to understand the impact that exposure to corruption news from the brazilian political scenario, has in the accceptability and intention in the consumer dysfunctional behavior (CDB). This dissertation was formulated to understand if after being exposed to corruption reports consumers tend to accept less and have less intention of having dishonest behavior. In the view of the above, two experimental studies were conducted online, via, Qualtrics, to test six hypotesis. As a result of the first study we found the negative effect that exposure to corruption news has on the acceptability and intent of CDB; in the second study the effect on the perception of justice of the reported punishments was verified, the punishments considered fair presented greater intention and acceptability of CDB in relation to the punishments considered unfair. Among the contributions of this research is the importance of investigating the impact that the political scenario has on consumer ethics, more specifically the exposure to corruption; the evidence that consumer ethical beliefs have no impact on the relationship of exposure to corruption news about acceptability and intent of CDB; the effect of the perceived justice of the punishments reported; and the finding that punishment perceived to be fair has a positive impact on acceptability and the intent of CDB, in comparison with the punshment perceived as unfair. Practical and theoretical contributions are found at the end of the paper, along with suggestions for future researchs.